Membrane attachment of Slr0006 in Synechocystis sp PCC 6803 is determined by divalent ions - Carmel D; Mulo P; Battchikova N; Aro EM (SPRINGER, 2022)
Slr0006 is one of the Synechocystis sp. PCC 6803 proteins strongly induced under carbon limiting conditions. Slr0006 has no predicted transmembrane helices or signal peptide sequence, yet it was exclusively recovered in the membrane fraction of Synechocystis, when the cells were broken in isolation buffers which contain divalent cations and are generally used for photosynthesis studies. Even subsequent washing of the membranes with high salt or various detergents did not release Slr0006, indicating strong binding of the Slr0006 protein to the membranes. Further, DNAse or RNAse treatment did not disturb the tight binding of Slr0006 protein to the membranes. Nevertheless, when the cells were broken in the absence of divalent cations, Slr0006 remained completely soluble. Binding of the Slr0006 to the membrane could not be properly reconstituted if the cations were added after breaking the cells in the absence of divalent ions. This unusual phenomenon has to be considered in identification and localization of other yet uncharacterized cyanobacterial proteins.